Német népcsoportjog a „dunai Európában“ : Egy nemzetszocialista jogátadás transznacionális összehasonlítása - Albrecht, Timo Marcel (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
This article addresses the transfer of the jurisprudentially developed National Socialist ‘Volksgruppenrecht’ (ethnic group law) into the legislation of east-central and southeastern European states from 1939 onwards. For the first time and using a systematic comparative and transnational perspective, the main legal consequences of the ‘völkisch New Order of Europe’ for the German minorities in most of the ‘Greater German Reich’s’ eastern allies are presented, analysed and contextualised. After localising the contemporary concept of ‘Donaueuropa’ (‘Danube Europe’), which was charged with Nazi spatial plans and included Slovakia, Hungary, Romania, Croatia as well as Serbia, and outlining the jurisprudential foundations of the Nazi ‘Volksgruppenrecht’, the study focuses predominantly on the respective domestic legislations. Thereby, a clear connection to the ‘völkisch’-imperialist goals of the ‘Third Reich’ and its hegemony in the southeast of the proclaimed ‘Großraum’ becomes apparent – for example in the transnational expansion of the German ‘Volksgemeinschaft’ as well as in the Nazi ‘Gleichschaltung’ of German ethnic groups on the basis of the new ‘Volksgruppenrecht’, but also in the replacement of the liberal minority protection system of the League of Nations era and the mass recruitment of ethnic Germans for the Waffen-Ss.